Rust stains' response to environmental stresses: An experimental study on porcine skin. (October 2022) - Tomassini, Luca; Manta, Anna Maria; Naso, Ines; Adelini, Virginia; Paolini, Daniele; Petrasso, Pia Eugenia Ylenia; Piras, Gianluca Niccolò; Ciallella, Costantino
Abstract: Rust stains are rare marks typically caused by prolonged contact between skin and the iron components of the firearm. This study was aimed at showing how cutaneous iron deposits respond to physical and chemical changes that usually affect the integrity of biological tissues. Four samples of porcine skin were placed in contact with an iron plate. They were exposed to different stress conditions: carbonization, water immersion, sunlight exposure and burial. All the skin sections were stained with Hematoxylin and Eosin (H&E) and Perls Prussian Blue (PPB). The response to the different treatments was consistent among the skin sections, as none of the rust stains were significantly altered by the applied stresses. All the samples showed focal iron deposition in the examined sections, which appeared as blue-colored spots in a rose-to-red background. Rust mark formation is an "all or nothing" phenomenon leading to the appearance of a sign that is relatively fixed and cannot be easily modified by the most common environmental conditions. This feature suggests the permanence of rust stains both from a macroscopic and a microscopic point of view, using Perls Prussian Blue staining after the exposure of the skin samples to various environmental stresses within precise time intervals. Highlights: Rust stains: an endurable sign? Rust stains: classic forensic sign whose applications are yet to be found. Rust stains experimental recreation using porcine skin and iron plate: a proposal.